The Role of Intrinsic Motivation in Mediating the Effect of Occupational Self-Efficacy on South Kalimantan National Narcotics Agency Officers’ Work Engagement in Banjarmasin - Suyatno Suyatno; Nur Zata Yusrina; Claudia, Meiske; Dahniar Dahniar (Open Access Indonesia Journal of Social Sciences, 2023)
The consequences of the main tasks and functions of the provincial National Narcotics Agency (NNA) in the program of prevention, eradication, abuse, and illicit narcotics (P4GN) require the availability of reliable human resources who enjoy their work and are therefore closely tied to their work. Employees who have a sense of attachment to their work enable the implementation of their main duties, both as a team and individually. A solid team certainly consists of individuals who like their work and who have engagement with their work. This study was conducted to analyze the role of intrinsic motivation in mediating the effect of occupational self-efficacy on National Narcotics Agency (NNA) Officers' work engagement in Banjarmasin (South Kalimantan). The research population was equal to its sample size, including 61 NNA employees, whereas the sample size was taken using a total sampling technique. Data was collected through a survey by distributing questionnaires via Google Forms. Data was analyzed with path analysis techniques using SPSS version 26. The findings show that self-efficacy has a significant positive effect on intrinsic motivation and work engagement. Intrinsic motivation significantly affects employees’ work engagement. Intrinsic motivation significantly and partially mediates the influence of occupational self-efficacy on NNA employee’s work engagement.